Lactose hydrolysis by free and fibre-entrapped β-galactosidase from Streptococcus thermophilus - Zhennai Yang (Agricultural and Food Science, 1993)
To study lactose hydrolysis by β-galactosidase, this enzyme was produced from Streptococcus thermophilus strain 11F and partially purified by acetone and ammonium sulphate fractionation, and ion exchange chromatography on a Q Sepharose FF column. Lactose hydrolysis by the enzyme was affected by lactose concentrations, sugars and milk proteins. The maximum extent of lactose hydrolysis in buffer was obtained with a 15% lactose concentration. Addition of 2% of lactose, glucose, galactose or sucrose in milk inhibited the enzymatic hydrolysis. The enzyme was activated by bovine serum albumin and a combination of αs-casein and β-casein. Of the casein fractions, the principal fraction, αs-casein, was less effective than β-casein and κ-casein. The fibre entrapped enzyme had a temperature optimum of 57°C, and a pH optimum from 7.5 to at least 9.0 with O-nitrophenyl-β-D-galactopyranoside as substrate. By recycling with whey and skim milk through a jacketed glass column (1.6 cm x 30 cm) loaded with fibre-entrapped enzyme at 55°C, a lactose hydrolysis of 49.5% and 47.9% was achieved in 11 h and 7 h respectively.